Steroid Elimination—Who, When, How? - Matas, A.J. (2008)
Steroids have numerous side effects, many occurring early posttransplantation with relatively low prednisone doses. Consequently, investigators have attempted steroid minimization or withdrawal. The first attempts at steroid minimization used early low-dose steroids and were associated with an increased rate of acute rejection episodes, late graft dysfunction, and graft loss. Subsequent studies, with cyclosporine-based immunosuppression, attempted steroid withdrawal late posttransplantation (>3 months) in highly selected, clinically well, and immunologically low-risk recipients. Again, steroid withdrawal was associated with an increased risk of acute rejection episodes and these episodes were associated with graft dysfunction and increased graft loss. The development of new powerful immunosuppressive agents has led to renewed attempts at late prednisone withdrawal. These also have been associated with increased late rejection risk. A more exciting innovation has been the attempts at rapid discontinuation (≤7 days posttransplantation) of prednisone with the following results: (1) Randomized studies have shown no significantly increased risk of acute rejection; (2) Randomized and nonrandomized studies have shown no increase in late graft loss; (3) Successful use in living and deceased donor recipients, primary and re–transplant recipients, adult and child recipients, white and black recipients, and low-risk and highly sensitized recipients; (4) About 80% of recipients remain prednisone-free long term. Recent nonrandomized data suggest that recipients who have an acute rejection episode while prednisone free are more likely to have a second rejection episode if they are returned to prednisone-free immunosuppression. In these cases the acute rejection episode should be treated and long-term prednisone continued at 5 mg/d.